2020
DOI: 10.1097/md.0000000000023698
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of modified Yupingfeng formula in treating allergic rhinitis

Abstract: Background: Allergic rhinitis (AR) is a non-infectious chronic nasal mucosal disease mediated mainly by IgE, which affects 40% of the global population and has a recurrence rate of more than 50%. The modified Yupingfeng formula (MYPFF) is widely used in the treatment of allergic rhinitis in China. However, there is no evidence-based medical evidence for the efficacy and safety of MYPFF in the treatment of allergic rhinitis. Methods: Database as China National Knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…YuPingFeng (YPF), one of the classic TCM formulas with a tonic effect, is composed of Astragali Radix, Atractylodes Macrocephala Koidz, and Radix Saposhnikoviae. Recent pharmacological studies have shown that YPF can activate mucosal immunity, resists hormone-induced immunosuppression, and is recommended to be used in the treatment of stable COPD [ 13 , 14 ]. A multicentre, randomized, double-blind, placebo-controlled clinical study we conducted confirmed that the combination of conventional treatment with YPF granules for 52 weeks significantly reduced the risk of acute exacerbations by 32.3% in moderate-to-severe COPD patients [ 15 ], but did not investigate the mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…YuPingFeng (YPF), one of the classic TCM formulas with a tonic effect, is composed of Astragali Radix, Atractylodes Macrocephala Koidz, and Radix Saposhnikoviae. Recent pharmacological studies have shown that YPF can activate mucosal immunity, resists hormone-induced immunosuppression, and is recommended to be used in the treatment of stable COPD [ 13 , 14 ]. A multicentre, randomized, double-blind, placebo-controlled clinical study we conducted confirmed that the combination of conventional treatment with YPF granules for 52 weeks significantly reduced the risk of acute exacerbations by 32.3% in moderate-to-severe COPD patients [ 15 ], but did not investigate the mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Yu-Ping-Feng-San (YPF) is a compound traditional Chinese medicine extensively prescribed to treat respiratory diseases such as upper respiratory tract infection (Song et al, 2016), asthma (Wang et al, 2020), allergic rhinitis (Liao et al, 2020), and chronic obstructive pulmonary disease (Ma et al, 2018), and contains Astragalus mongholicus Bunge, Atractylodes macrocephala Koidz., and Saposhnikovia divaricata (Turcz. ex Ledeb.)…”
Section: Introductionmentioning
confidence: 99%
“…Yupingfeng Powder (YPFP) originated from the ancient Chinese medicine book "Danxi Xinfa," which is composed of three Chinese herbs: Huangqi, Fangfeng, and Baizhu. In allergic diseases, YPFP shows good effects on both improving symptoms and controlling recurrence [11][12][13]. It has been confirmed that the glycoside extract of YPFP exerts antiinflammatory and immunological functions by regulating T lymphocyte differentiation subtypes [14].…”
Section: Introductionmentioning
confidence: 99%